Aggressive movement detection using optical flow features base on digital & thermal camera - Tan Zizi @ Tuan Zizi, Tuan Khalisah; Ramli, Suzaimah; Mohd Zainudin, Norulzahrah; Hasbullah, Nor Asiakin; Abdul Wahab, Norshariah; Mat Razali, Noor Afiza; Ibrahim, Norazlin (2017)
Detection and tracking of people in digital images has been subject to extensive research in the past decades.Following the growing availability of thermal cameras and the distinctive thermal signature of humans, research effort has been focusing on developing people detection and tracking methodologies applicable to this sensing modality.Thermal imaging technology can be used to detect aggressive levels in humans based on the radiated heat from their face and body. Previous research proposed an approach to figure out human aggressive features using Horn-Schunck optical flow algorithm in order to find the flow vector for all video frames using digital camera only. However, still not strong enough to confirm and verify the existence of an aggressive movement. Then, we propose another approach using thermal videos to detect aggressive features in human aggressive movement.Video frames are collected using thermal camera and then extracted into thermal images. This research also guides and discovers the patterns of body distracted movement.Result below will show the comparison between both cameras digital and thermal camera.